Clinical outcomes in peritoneal dialysis with refractory peritonitis: significance of the day 5 cell count - BERKE MENTEŞE, İLAY; BARUTÇU ATAŞ, DİLEK; TUĞCU, MURAT; ARIKAN, İZZET HAKKI; VELİOĞLU, ARZU; AŞICIOĞLU, EBRU (My University, 2024)
Background: Peritoneal dialysis-associated peritonitis is a common and severe complication of peritoneal dialysis, associated with high morbidity and mortality. However, there’s a lack of research on refractory peritonitis, which is difficult to manage and has a poor prognosis. Our study aimed to investigate factors affecting clinical outcomes in peritoneal dialysis patients with refractory peritonitis over a 12-year period at a medical faculty hospital in Turkey. Methods: We conducted a retrospective study at a single center from January 2009 to December 2020, involving 135 patients with 236 episodes of refractory peritonitis. The average age of the patient cohort was 53.0 ± 15.9 years, and 72 (53.4%) of the patients were male. The leading identified causes of end-stage kidney disease were glomerulonephritis, hypertensive glomerulosclerosis, and diabetic nephropathy. Data on microbiological etiology, dialysate white blood cell counts, and patient demographics were analyzed to identify catheter removal risk factors. Statistical significance was set at p ≤ 0.05. Results: Comparative analysis between patients with and without catheter loss revealed no significant differences in gender, age, presence of diabetes, prior hemodialysis, or duration of peritoneal dialysis. However, multivariate logistic regression analysis showed that a dialysate white blood cell count exceeding 1000/mm3 on day 5 and hospitalization had a positive association with catheter loss, while the presence of gram-positive bacterial growth had an inverse correlation. Conclusion: Our study shows that fifth-day dialysate white blood cell count predicts refractory peritonitis outcomes. Future research should focus on developing tools to manage catheter removal proactively and enhance patient prognosis.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Nefroloji; Yaşam Bilimleri; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyokimya; Fizyoloji; Temel Bilimler; Medicine; Internal Medicine Sciences; Internal Diseases; Nephrology; Life Sciences; Health Sciences; Fundamental Medical Sciences; Biochemistry; Human Physiology; Natural Sciences; Klinik Tıp (Med); Yaşam Bilimleri (Life); Klinik Tıp; Biyoloji Ve Biyokimya; Üroloji Ve Nefroloji; Clinical Medicine (Med); Life Sciences (Life); Clinical Medicine; Biology & Biochemistry; Urology & Nephrology; Physiology; Fizyoloji (tıbbi); Physiology (medical); End-stage kidney disease; Peritoneal dialysis; Refractory peritonitis